2023
DOI: 10.1021/acs.iecr.3c02113
|View full text |Cite
|
Sign up to set email alerts
|

PtBi Intermetallic Compounds with Enhanced Stability towards Base-Free Selective Oxidation of Glycerol

Yihua Sun,
Zhiyi Yu,
Wenyao Chen
et al.

Abstract: Designing efficient and stable catalysts for base-free oxidation of glycerol toward targeted products is highly desirable but remains challenging. Herein, carbon nanotube (CNT)-supported PtBi-ordered intermetallic compounds (O-PtBi/CNT) were prepared with the aim of enhancing their catalytic performance in preferential oxidation of the secondary hydroxyl group of glycerol. Performance tests show that the O-PtBi/CNT catalyst with high percentage of Pt0 species and ordered atomic distribution affords high select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Regulating the Pt site via introducing a second metal promoter is the most widely adopted strategy for enhancing the catalytic performance . Such bimetallic catalysts display unique geometry coordination environments and electronic structures that are different from the parent Pt metal. In particular, Pt-based intermetallic compounds (IMCs), such as the tetragonal L10-type PtM with heterometal atoms bonded, can be varied to a limited extent while still maintaining a highly structured lattice structure with a large number of interatomic bonding bonds, accompanied by a strong d–d orbital interaction. Therefore, they have been widely used in polyol oxidation and CO 2 hydrogenation reactions. For instance, Feng et al found that the introduction of Bi to Pt can induce the formation of a Pt–Bi active structure, promoting selective oxidation of the C–H bond on glycerol. Guo et al reported that reducing the exposure of surface Pd sites by introducing Cu maintains the high C–H bond activation ability and simultaneously inhibits the C–C bond cleavage for the oxidation of isopropanol to acetone.…”
Section: Introductionmentioning
confidence: 99%
“…Regulating the Pt site via introducing a second metal promoter is the most widely adopted strategy for enhancing the catalytic performance . Such bimetallic catalysts display unique geometry coordination environments and electronic structures that are different from the parent Pt metal. In particular, Pt-based intermetallic compounds (IMCs), such as the tetragonal L10-type PtM with heterometal atoms bonded, can be varied to a limited extent while still maintaining a highly structured lattice structure with a large number of interatomic bonding bonds, accompanied by a strong d–d orbital interaction. Therefore, they have been widely used in polyol oxidation and CO 2 hydrogenation reactions. For instance, Feng et al found that the introduction of Bi to Pt can induce the formation of a Pt–Bi active structure, promoting selective oxidation of the C–H bond on glycerol. Guo et al reported that reducing the exposure of surface Pd sites by introducing Cu maintains the high C–H bond activation ability and simultaneously inhibits the C–C bond cleavage for the oxidation of isopropanol to acetone.…”
Section: Introductionmentioning
confidence: 99%